Natural experiments: should we define them broadly or narrowly? - Peter Craig (Journal of Epidemiology and Community Health, 2026)
The recently updated UK Medical Research Council’s guidance on the use of natural experiments to evaluate population health interventions, published in 2025, adopted a broad definition of natural experiments as any event or process that divides a population into groups that differ in their exposure to the intervention of interest and that is not under the control of a researcher. Many authors adopt narrower definitions that only include cases where exposure is determined in an ‘as-if random’ or ‘plausibly exogenous’ way. I explain why we used a broad definition in our guidance, why narrower definitions are hard to apply consistently and what might be gained or lost by adopting a broad or a narrow one.